A Phase Transition Oxide/Graphene Interface for Incident‐Angle‐Agile, Ultrabroadband, and Deep THz Modulation. Issue 24 (4th November 2020) - Zhu, Hongfu; Li, Jiang; Du, Lianghui; Huang, Wanxia; Liu, Jingbo; Zhou, Jinhao; Chen, Yuanfu; Das, Sujit; Shi, Qiwu; Zhu, Liguo; Liu, Cangli
Abstract: Although plenty of functional materials have been explored to dynamically control the terahertz (THz) transmission, the limits in modulation depth, operation bandwidth, or angle‐agile characteristics hinder their applications in highly active THz devices. Here, a 2D/3D (graphene/phase transition oxide VO2 ) interface is demonstrated for unprecedented high‐efficiency modulation of THz waves with incident‐angle‐agile and ultrabroadband. An impedance matching state can be met at the graphene/VO2 interface by adjusting the stacked graphene layers, which leads to a minimal terahertz reflection amplitude. Then the interfacial impedance can be changed continuously via the semiconductor–metal phase transition of VO2 and achieve a THz switching. Based on this mechanism, this heterostructure demonstrates giant THz average amplitude modulation of 93%, 94%, and 96% in 0.3–1.5 THz at the incident angle of 35°, 48°, and 53°, respectively. Moreover, the corresponding insertion loss is only −7.4, −4.1, and −6.5, which is much lower than most of the present THz modulation. These coupling phenomena and functions arising from the integration of 2D material and 3D phase transition oxide film broaden the previous materials system for dynamic controlling of THz wave, and would promote advanced THz smart devices for practical applications. Abstract : An incident‐angle‐agile, ultrabroadband, and deep THz modulation is achieved at the phase transition oxide/graphene interface based on the impedance matching mechanism. The 2l graphene/VO2 heterostructure reaches a maximum THz amplitude modulation as high as 99.93% and average modulation depth of 93%, 94%, and 96% in 0.3–1.5 THz at the incident angle of 35°, 48°, and 53°, respectively.